THE GUARANÍ MILITIAS IN THE JESUIT MISSIONS OF PARAGUAY AND RÍO DE LA PLATA: A CASE STUDY OF THE TRANSITION OF MILITARY ORGANIZATION AND TACTICS FROM EARLY MODERN SPAIN TO ITS OVERSEAS POSSESSIONS - Takeda, Kazuhisa (Revista de Historia Social y de las Mentalidades, 2017)
In the context of the military history of early modern Spain, this article argues that the militia organized by the Guaraní Indians under the supervision of the Jesuits in the Río de la Plata area, was intended for the purpose of tracing the transference of military organization and tactics from the Spanish monarchy to its overseas colonies. The principal documents analyzed in this article are a number of guidebooks having reference to military theory and techniques, published in Spain and other European regions, and written orders of military exercise transmitted by successive Jesuit superiors to the indigenous peoples in the River Plate region. The Spanish and Guaraní soldiers shared the same mode of forming military units called “Companies”, and in the battlefield they organized a number of well-ordered military formations called “Squadrons”